Evaluation of physicochemical, in vivo analgesic and antiinflammatory activities of Brachystegia eurycoma gum-based naproxen loaded niosomal gels - Sinodukoo Eziuzo Okafo; John Ikechi Ordu; Godfrey Ofagbor; Emmanuel Agbamu (German Journal of Pharmaceuticals and Biomaterials, 2023)
Protracted oral Naproxen administration for acute and chronic conditions, such as rheumatoid arthritis treatment, may cause peptic ulcers. The topical application of Naproxen will circumvent this effect. This research aims to assess the physicochemical, anti-inflammatory and analgesic properties of Naproxen-loaded niosomal gels formulated using Brachystegia eurycoma gum (BEG) as the gelling polymer. BEG was isolated by acetone precipitation of filtrate produced by cold maceration of Brachystegia eurycoma seeds powder. Naproxen and BEG compatibility was evaluated using Fourier transform infrared FTIR) spectroscopy. Naproxen-loaded niosomes were produced with cholesterol, surfactant (tween 80) and water using a modified ethanol injection method. The formulated niosomes were incorporated into either BEG (5, 7.5 or 10%) or HPMC (1.5, 5%) gel base to produce the respective Naproxen-loaded niosomal gels. The niosomal gels were assessed for their physicochemical, antiinflammatory and analgesic properties using a commercially available gel as a positive control. There was no incompatibility between BEG and Naproxen. The formulated gels' pH ranged from 6.4 to 7.3, while the viscosity ranged from 1476.2 to 2980 mPas. The formulated gels had good extrudability and spreadability compared to the commercially available gel (1%). In-vivo studies using white albino rats showed that gels from the optimized formulation (F1) had comparable anti-inflammatory (26.5% inhibition) and analgesic properties to the commercially available gel (31.3% inhibition). Naproxen-loaded niosomal gels having good physicochemical, analgesic and anti-inflammatory properties were successfully formulated using BEG as a gelling agent.